The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.2514/3.20616
|View full text |Cite
|
Sign up to set email alerts
|

Weak Hamiltonian finite element method for optimal control problems

Abstract: A temporal finite element method based on a mised form of the Hamiltonian n-eal; principle is developed for dynamics and optimal control problems. The mixed form of Hamilton's weak principle contains both displacements and momenta as primary variables that are expanded in terms of nodal values and simple polynomial shape functions. Unlike other forms of Hamilton's principle, however, time derivatives of the nionient a and displacements do not appear therein; instead, only the virtual momenta and virtual displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…DFET was initially proposed in [8] and uses finite elements in time on spectral bases to transcribe the differential equations into a set of algebraic equations. Finite Elements in Time for the indirect solution of optimal control problems were initially proposed by Hodges et al in [9], and during the late 1990s evolved to the discontinuous version. As pointed out by Bottasso et al in [10], FET for the forward integration of ordinary differential equations are equivalent to some classes of implicit RungeKutta integration schemes, can be extended to arbitrary highorder, are very robust and allow full h-p adaptivity.…”
Section: Problem Transcriptionmentioning
confidence: 99%
“…DFET was initially proposed in [8] and uses finite elements in time on spectral bases to transcribe the differential equations into a set of algebraic equations. Finite Elements in Time for the indirect solution of optimal control problems were initially proposed by Hodges et al in [9], and during the late 1990s evolved to the discontinuous version. As pointed out by Bottasso et al in [10], FET for the forward integration of ordinary differential equations are equivalent to some classes of implicit RungeKutta integration schemes, can be extended to arbitrary highorder, are very robust and allow full h-p adaptivity.…”
Section: Problem Transcriptionmentioning
confidence: 99%
“…Dynamics community have also considered this type of approach in regard to various applications such as structural dynamics, nonlinear vibrations, inverse dynamics of flexible robots, gate analysis, and optimal control problem for converting problems from infinite dimension to finite dimension. Some of the related works can be found in [23]- [29]. These prior time-parameterization methods often produced highly nonlinear and coupled sets of equations, thus limiting their tractability with complex systems.…”
Section: State-time Vs Traditional State Dynamic Formulationsmentioning
confidence: 99%
“…Riff and Baruch [9] [15,29] demonstrated that a mixed finite element formulation (where generalized coordinates and their momenta appear as independent unknowns) yields solutions with unconditional stability without having to use reduced element quadrature. The current research is also based on a mixed finite element formulation.…”
Section: Hamilton's Lawmentioning
confidence: 99%
“…Because there are no derivatives, only simple shape functions are necessary to satisfy C 0 continuity between elements. Higher order elements (p elements) could also be developed; however, for general nonlinear problems the use of crude shape functions is more efficient in that it allows element quadrature to be performed by inspection [29]. Independent variables need only be piecewise continuous, while variational quantities must be continuous and piecewise differentiable.…”
Section: Hamilton's Weak Principlementioning
confidence: 99%
See 1 more Smart Citation